INT-react: An O(E) Path Planner for Resilient Network-Wide Telemetry Over Megascale Networks - Yuan, Qianchen; Li, Fuliang; Pan, Tian; Xu, Yifan; Wang, Xingwei (Proceedings - International Conference on Network Protocols, 2022)
In-band network telemetry (INT) delivers high-precision network monitoring by collecting device-internal states entirely on the data plane. For rapid congestion awareness and network troubleshooting, it is necessary to conduct network-wide telemetry by generating multiple monitoring paths covering the entire network graph. Solving the optimal path planning problem used the eulerian trail initially at a time complexity of O(k(3E+V-15k/2)) . For mega-scale data center networks, such a high complexity is unacceptable because the algorithm cannot adapt well to occasional topology changes. In this work, we propose improved INT-path and INT-react, two refined path planning algorithms with a much reduced time complexity of only O(E) . Furthermore, INT-react also considers balanced path generation to reduce the longest path length for synchronized collection of telemetry data from each monitoring path. The evaluation shows that on average it costs 2.10s for the improved INT-path to solve the optimal path planning for a network of 9500 switches, while the computation is completed within only 0.283s on average for INT-react. In addition, INT-react reduces the longest path length. INT-react's path planning is so fast that it promptly reacts to topology changes and is ready to be deployed in mega-scale production networks.